2013
DOI: 10.1007/978-3-642-35697-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Are International Food Price Spikes the Source of Egypt’s High Inflation?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Perubahan harga barang dan jasa dapat berdampak pada kondisi perekonomian, termasuk perubahan bahan pangan pokok. Kenaikan harga bahan pangan dapat berkontribusi terhadap inflasi suatu negara (Al-Shawarby & Selim, 2013). Menurut (Widiarsih, 2012), harga beras berpengaruh signifikan terhadap Inflasi bahan makanan baik dalam jangka panjang maupun jangka pendek yang ditandai dengan nilai koefisien regresi yang bertanda positif.…”
Section: Pendahuluanunclassified
“…Perubahan harga barang dan jasa dapat berdampak pada kondisi perekonomian, termasuk perubahan bahan pangan pokok. Kenaikan harga bahan pangan dapat berkontribusi terhadap inflasi suatu negara (Al-Shawarby & Selim, 2013). Menurut (Widiarsih, 2012), harga beras berpengaruh signifikan terhadap Inflasi bahan makanan baik dalam jangka panjang maupun jangka pendek yang ditandai dengan nilai koefisien regresi yang bertanda positif.…”
Section: Pendahuluanunclassified
“…Changes in commodity and service prices may affect economic requirements, including changes in Food materials. Rising food prices can contribute to country inflation (Al-Shawarby and Selim, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…IMF 2012: 55). As to the effect of international food price inflation on domestic food price inflation, it was found that “short-term pass-through” was relatively high between 2001 and 2011, “with more than a quarter of the external shock (29 percent) passing through to food inflation after 6 months and around two-thirds after a year” (Al-Shawarby and Selim 2012: 20). In the years before the 2011 revolution, the development of domestic food prices showed, indeed, considerable peaks (Table 2).…”
Section: Introduction: the Egyptians’ Call For Bread Freedom And Social Justicementioning
confidence: 99%